Regular spectral problem for conformable Dirac system with simulation analysis - Ercan, Ahu; Bas, Erdal (Taylor & Francis Ltd, 2021)
In this study, we give some essential spectral data for conformable Dirac system with seperated boundary conditions. The given spectral data like representation of solutions, asymptotic formulas of eigen-vector-functions and eigenvalues and their normalized forms are applied in light of limit based local derivative. The representations of the solutions are obtained by using two different methods. Also, we compare the solutions with graphics under different orders, different eigenvalues, different potentials. At the end of the article, an extensive assessment is performed about the results by taking into account the behaviours of the eigen-vector-functions and the eigenvalues.
Keywords: Dirac operator; Conformable derivative; Asymptotic formula; Spectral problem; Eigenvalues